2018
DOI: 10.1111/mcn.12692
|View full text |Cite
|
Sign up to set email alerts
|

Intake, sources, and determinants of free sugars intake in Australian children aged 12–14 months

Abstract: The consumption of free sugars is directly associated with adiposity and dental caries in early childhood; however, intake data in the first 2 years of life are limited. This cross-sectional analysis aims to identify major food sources of free sugars for Australian children aged 12-14 months and investigate factors associated with meeting the World Health Organisation (WHO) Guideline for sugars intake. Three days of nonconsecutive dietary data were collected via a 24-hr recall and 2-day food record for 828 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 41 publications
4
33
0
Order By: Relevance
“…Koh et al reported that Australian and British mothers were more likely to introduce hot chips/ French fries early in the weaning period than women born in other countries [18]. Similarly, in an earlier analysis of the SMILE data we reported that at 12 to 14 months of age, sons of women born in Australia were more likely than sons of women born in other countries to exceed the WHO recommendation that less than 5% of total energy should be derived from free sugars [59]; but this association was not significant for daughters.…”
Section: Discussionsupporting
confidence: 55%
“…Koh et al reported that Australian and British mothers were more likely to introduce hot chips/ French fries early in the weaning period than women born in other countries [18]. Similarly, in an earlier analysis of the SMILE data we reported that at 12 to 14 months of age, sons of women born in Australia were more likely than sons of women born in other countries to exceed the WHO recommendation that less than 5% of total energy should be derived from free sugars [59]; but this association was not significant for daughters.…”
Section: Discussionsupporting
confidence: 55%
“…At present, little is known about when and in what forms free sugars enter the diet, as children move through the weaning period towards a dietary pattern reflective of their family’s diet. Free sugars intakes at 1 year of age have recently been reported for participants in the Study of Mothers’ and Infants’ Life Events affecting oral health (SMILE) [22]. This research extends this work to report findings for the same cohort at 2 years of age.…”
Section: Introductionsupporting
confidence: 66%
“…Children from households with the greatest socioeconomic disadvantage were more likely to exceed the WHO recommendations that <10% of energy should come from free sugars than the least disadvantaged. 30 Those children were also more likely to be in the top tertile for free sugars intake (PR: 1.58 (1.19–2.10)) than the least disadvantaged. Further differences in health behaviours and practices beyond free sugars intake have been found according to sociodemographic factors.…”
Section: Key Findings To Datementioning
confidence: 98%
“… 29 Between 1 and 2 years, intake of free sugars increased sharply, contributing 3.6% (IQR: 1.6–4.8) of total energy intake at 1 and 22.5% at 2 years (IQR: 12.8–37.7). 30 The proportion of participants that exceeded the WHO recommendations that <10% of energy should come from free sugars 9 increased substantially from 1 (2.5%) to 2 years (38.0%). A quarter of participants exceeded the WHO <5% energy from free sugars recommendation 9 at 1 year, increasing to 71.1% at 2 years.…”
Section: Key Findings To Datementioning
confidence: 99%
See 1 more Smart Citation